Integrating the Maqasid Shariah and Green Constitution Approaches in Addressing Illegal Investment: An Analysis of the Dynamics of National Legal Reform - Novianti, Linda; Setiawati, Liya; Rahmadika, Sarah; Nurrohmat, Asep Gema (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the integration of Maqashid Shariah and the Green Constitution as a conceptual framework for reforming Indonesia’s legal system in response to the growing threat of illicit investment. Utilizing a normative-juridical approach and a descriptive qualitative method, the research is based on primary sources including statutory regulations and constitutional provisions, as well as secondary materials such as Islamic jurisprudence, academic journals, and legal documents. The findings demonstrate that reactive legal enforcement alone is insufficient to combat the complexity of investment-related fraud. The principle of ḥifẓ al-māl in Maqashid Shariah highlights the ethical imperative to protect wealth proactively, advocating for transparency, equity, and distributive justice in financial regulation. Simultaneously, the Green Constitution anchors environmental sustainability and social justice as constitutional obligations, emphasizing the role of law in safeguarding both present and future generations from systemic economic harm. Together, these two frameworks form a transdisciplinary legal model that transcends legal formalism by incorporating moral, spiritual, and ecological values into investment governance. The study concludes that national legal reform must adopt an integrative approach to ensure not only legal certainty, but also ethical legitimacy and sustainable public welfare. This conceptual synthesis contributes to the evolving global discourse on ethical finance and constitutional justice, offering practical recommendations for policymakers, academics, and regulatory institutions in developing fair and preventive investment laws.